A Condensing Enzyme from the Seeds of Lesquerella fendleri That Specifically Elongates Hydroxy Fatty Acids - Moon, Hangsik (American Society of Plant Physiologists, 2001)
Lesquerella fendleri seed oil contains up to 60% hydroxy fatty acids, nearly all of which is the 20-carbon hydroxy fatty acid lesquerolic acid (d-14-hydroxyeicos-cis-11-enoic acid). Previous work suggested that lesquerolic acid in L. fendleri was formed by the elongation of the 18-carbon hydroxy fatty acid, ricinoleic acid. To identify a gene encoding the enzyme involved in hydroxy fatty acid elongation, an L. fendleri genomic DNA library was screened using the coding region of the Arabidopsis Fatty Acid Elongation1 gene as a probe. A gene, LfKCS3, with a high sequence similarity to known very long-chain fatty acid condensing enzymes, was isolated. LfKCS3 has a 2,062-bp open reading frame interrupted by two introns, which encodes a polypeptide of 496 amino acids. LfKCS3 transcripts accumulated only in the embryos of L. fendleri and first appeared in the early stages of development. Fusion of the LfKCS3 promoter to the uidA reporter gene and expression in transgenic Arabidopsis resulted in a high level of β-glucuronidase activity exclusively in developing embryos. Seeds of Arabidopsis plants transformed with LfKCS3 showed no change in their very long-chain fatty acid content. However, when these Arabidopsis plants were crossed with the transgenic plants expressing the castor oleate 12-hydroxylase, significant amounts of 20-carbon hydroxy fatty acids accumulated in the seed, indicating that the LfKCS3 condensing enzyme specifically catalyzes elongation of 18-carbon hydroxy fatty acids.